Relationship between 2 standardized tackling proficiency tests and rugby league match-play tackle performance - Speranza, M. J. A.; Gabbett, T. J.; Greene, D. A.; Johnston, R. D.; Townshend, A. D. (International Journal of Sports Physiology and Performance, 2018)
This study investigated the relationship between 2 different assessments of tackling ability, physical qualities, and match-play performance in semiprofessional rugby league players. A total of 18 semiprofessional rugby league players (mean [SD]: age=23.1 [2.0] y and body mass=98.8 [11.8] kg) underwent tests of upper- and lower-body strength and power. Tackling ability was assessed using video analysis of under- and over-the-ball tackle drills. A total of 2360 tackles were analyzed from match play. Over-the-ball tackle ability was positively related to the proportion of dominant tackles (Spearman rank-order correlation coefficients [rs]=.52; 95% confidence interval [CI] .07-.79, P=.03) and average play-the-ball speeds (rs=.50; 95% CI .04-.78, P=.03) and negatively related to tackles that conceded offloads (rs=-.55; 95% CI -.78 to .04, P=.04). Under-the-ball tackle ability was significantly related to the proportion of dominant tackles (rs=.57; 95% CI .14-.82, P=.01) and missed tackles (rs=-.48; 95% CI -.77 to .02, P=.05). Good over-the-ball tacklers performed proportionally more dominant tackles, allowed significantly fewer offloads, and had longer average play-the-ball speeds. Good under-the-ball tacklers missed proportionately fewer tackles. This study suggests that both the under-the-ball and over-the-ball standardized tackle assessments are associated with varying indicators of match-play tackle performance and justifies the practical utility of these tests to assess and develop both types of tackles.